Analysis of an analytical model to evaluate the interaction between a vibratory table and an essay structure, during seismic simulation tests - Patiño Mendoza, Carmen (2018)
In the present research work, an analytical model that evaluates the interaction between vibratory table and test structures, during seismic simulation tests is analyzed. The model under study is the one proposed by Esparza (1986), which represents the implementation of a controller by feedback of forces and displacement, with the purpose of expanding the study in vibratory tables that constitute crucial tools to analyze the performance of structures before seismic actions. It should be noted that these devices have become a fundamental part in the field of earthquake-resistant engineering, allowing us to study complex structural dynamical models. Based on an extensive literature review, this research paper describes and discusses some of the most commonly used control systems and their effect on the reproduction of the seismic signal on vibrating tables and, in the case of the test structure, opted to use a structure with cellular concrete properties, in order to validate its behavior against seismic events, as an efficient construction alternative and identify its dynamic parameters.